2014
DOI: 10.1017/s0266467414000509
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizas increase survival, precocity and flowering of herbaceous and shrubby species of early stages of tropical succession in pot cultivation

Abstract: Abstract:Arbuscular mycorrhizal fungi (AMF) are an important biotic factor that influences tropical ecological succession and differently affect the woody species belonging to different successional stages. However, little is known about the influence of AMF on growth and reproduction of herbaceous and shrubby species of early phases of tropical succession. Thus, we assessed the effect of AMF on the development of 27 heliophilous herbaceous and shrubby tropical species. Plants were grown in greenhouse, in low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Seeds were purchased from Isla Sementes (Porto Alegre, Brazil). Germination was performed in plastic pots (10.5 cm high, 9.5 cm lower diameter, 14 cm upper diameter) filled with a clay soil (a Rhodic Ferralsol) collected from an herbicide-free experimental area at the campus of the State University of Londrina, Brazil (for a detailed characterization of the soil, see [ 24 ]). One week after sowing, four individuals were retained in each pot and the substrate was supplemented with 50 mL of complete nutrient solution [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seeds were purchased from Isla Sementes (Porto Alegre, Brazil). Germination was performed in plastic pots (10.5 cm high, 9.5 cm lower diameter, 14 cm upper diameter) filled with a clay soil (a Rhodic Ferralsol) collected from an herbicide-free experimental area at the campus of the State University of Londrina, Brazil (for a detailed characterization of the soil, see [ 24 ]). One week after sowing, four individuals were retained in each pot and the substrate was supplemented with 50 mL of complete nutrient solution [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dense network produced by root systems of the exotic restricted seedling emergence of the heliophilous herbaceous and early-successional woody species because this plant species typically has small seeds that produce small and fragile seedlings (Rondina et al . 2014, Zangaro et al . 2003, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The soil was collected at 0-10 cm depth, sieved (2-mm mesh) and transferred to plastic pots with 3500 cm 3 capacity. Soil samples were airdried at room temperature and subjected to chemical analysis, as described in Rondina et al (2014). First, one third of the pots were sown with seeds of the exotic grass U. brizantha as a competitor, another third of the pots were sown with seeds of the forb L. nepetifolia as a competitor, and the remaining third of the pots were left without a competitor, as control.…”
Section: Soil Sampling Preparation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…When evaluating the yield of Marandu grass subjected to increasing doses of phosphorus, Porto EMV et al [31] also observed increases in dry matter production with the increment of P doses, reaffirming the significance of this nutrient in forage yield in phosphorus-deficient soils under pasture conditions [32,33].…”
Section: Yield and Morphological Characteristics Of Marandu Grassmentioning
confidence: 96%